A Guide to Sovereign Debt Data - Abbas, S. M. Ali (IMF Working Papers; Working Paper ;, 2019)
The last decade or so has seen a mushrooming of new sovereign debt databases covering long time spans for several countries. This represents an important breakthrough for economists who have long sought to, but been unable to tackle, first-order questions such as why countries have differential debt tolerance, and how debt levels affect the scope for countercyclical policy in recessions and financial crises. This paper backdrops these recent data efforts, identifying both the key innovations, as well as caveats that users should be aware of. A Directory of existing publicly-available sovereign debt databases, featuring compilations by institutions and individual researchers, is also included.